Informing an ICT intervention for HIV and AIDS education at Rhodes University - Gunzo, Fortunate Takawira (Rhodes University, Faculty of Education, Department of Education, 2010)
This study captures the process and methods used in selecting and organising content for an ontology. In the Information and Communication Technology (ICT) field ontology refers to a way of organising and storing information and facilitating interaction between the system and its users. Ontologies are being used more frequently to provide services that deal with complex information. In this study, I record my experience of developing content for an HIV and AIDS ontology for Rhodes University students. Using several different methods, I started the process of selecting and organising HIV and AIDS information, free of scientific jargon and prescriptive language, and consisting only of relevant information. I used data derived from interviews with six HIV and AIDS experts to develop questions for a survey that was open to all Rhodes University students. The 689 people who responded to the survey indicated that they needed more information on testing, treatment and living with HIV. Responses also showed that students had a lot of information on HIV prevention and transmission. Four focus group discussions revealed that students were tired of repetitions of the same"Ÿ information on HIV and AIDS and wanted to know more about life after contracting HIV. Using this data, I propose some guidelines to populate HIV and AIDS ontology. Ontologies can be customized for particular groups of users, for example according to gender, race, year of study etc. Another advantage of the ontology is that it can be expanded or contracted depending on the scope of one"Ÿs intervention.
Keywords: AIDS (Disease) -- Prevention -- South Africa; AIDS (Disease) -- Study and teaching -- South Africa; HIV infections -- Prevention -- South Africa; HIV infections -- Study and teaching -- South Africa; Health education -- South Africa; Educational technology -- South Africa; Rhodes University -- Students -- Attitudes; Counseling in higher education -- South Africa